2021
DOI: 10.1021/acs.biochem.1c00327
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Mechanism of 2′-Phosphorylation-Aided Amide Ligation in Peptidyl Nucleoside Biosynthesis

Abstract: Peptidyl nucleoside antifungals, represented by nikkomycins and polyoxins, consist of an unusual six-carbon nucleoside [aminohexuronic acid (AHA)] ligated to a nonproteinogenic amino acid via an amide bond. A recent study suggested that AHA is biosynthesized through cryptic phosphorylation, where a 2′-phosphate is introduced early in the pathway and required to form AHA. However, whether 2′-phosphorylation is necessary for the last step of biosynthesis, the formation of the amide bond between AHA and nonprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the nikkomycin and polyoxin pathways, AHA had long been thought of as a biosynthetic intermediate due to its accumulation in the culture medium of mutant strains that abolish the biosynthesis of the N-terminal amino acid moiety. However, the recent discovery of the cryptic phosphorylation 9 and subsequent kinetic characterization of the amide ligases 16 revealed that AHA is actually a shunt metabolite. Although a phosphatase has not been identified for either of these pathways, dephosphorylation most likely occurs at the end of the pathways.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In the nikkomycin and polyoxin pathways, AHA had long been thought of as a biosynthetic intermediate due to its accumulation in the culture medium of mutant strains that abolish the biosynthesis of the N-terminal amino acid moiety. However, the recent discovery of the cryptic phosphorylation 9 and subsequent kinetic characterization of the amide ligases 16 revealed that AHA is actually a shunt metabolite. Although a phosphatase has not been identified for either of these pathways, dephosphorylation most likely occurs at the end of the pathways.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Similar phosphorylation of biosynthetic intermediates was also found in some of the LipL‐containing pathways, such as muraymycin [43] and caprazamycin [34] biosynthesis, and has been proposed as a self‐resistance mechanism against the toxic effects of the biosynthetic intermediates. Although the role of 2'‐phosphorylation in the nikkomycin pathway is unclear, it is essential for the activities of the downstream enzymes and conserved in nikkomycin, polyoxin, and malayamycin pathways [24a,35a] . Since kinases with unknown functions are frequently found in many other nucleoside BGCs, [35b] similar cryptic phosphorylation is likely operating in other nucleoside pathways.…”
Section: Nucleosides Biosynthesized Through Radical‐mediated C5' Exte...mentioning
confidence: 99%
“…45 Nonetheless, the 2′-phosphorylation containing nucleoside skeleton ( 106 ) was subsequently affirmed as the physiological substrate of PolG and the cryptic phosphorylation is retained till the final step of polyoxin biosynthesis. 46 But the characterization of PolG is ambiguous whether this enzyme also assembles the nucleoside skeleton and POIA or not. In addition, the oxygenations of the 5-methyl group in the nucleoside skeleton to hydroxyl or carboxyl as found in polyoxins A, F and I are obscure, probably by a promiscuous oxygenase located outside of the pol cluster.…”
Section: Polyoxinsmentioning
confidence: 99%